Publisher Correction: Development of a genetically encodable FRET system using fluorescent RNA aptamers - Mette D. E. Jepsen (Nature Portfolio, 2018)
In the original version of this Article the last section of the Methods describing Fluorescence microscopy was inadvertently omitted during the production process. This has now been corrected in the PDF and HTML versions of the Article.